READING BASED-CLASSROOM ACTIVITIES: AN EFFORT TOWARD THE INTEGRATION OF LANGUAGE SKILLS IN TEACHING ENGLISH AS A FOREIGN LANGUAGE IN INDONESIA - Hadi Hadi (TEFLIN, 2006)
Abstract: This paper proposes the implementation of reading-based classroom activitiesÃÂ for teaching English as a foreign language in Indonesia. Compared to other language skills, reading is viewed to provide a relatively stable foundation for Indonesian students to develop their communicative competenceÃÂ in English. It is argued that reading-focused activities stimulate confidence for Indonesian learners to get involved in listening, speaking, and writing related-activities in ways that are similar to normal daily lifeÃÂ communication. The reasons for the proposed implementation of reading-based classroom activitiesÃÂ in TEFLINÃÂ and the role of reading and its relation with other language skills are presented.